Tribological behaviour of plasma electrolytic oxide coatings on Ti6Al4V and cp-Ti alloys. (2nd June 2016) - Tekin, K. C.; Malayoglu, U.; Shrestha, S.
Abstract : In this study, mechanical and tribological properties of plasma electrolytic oxide (PEO) coatings prepared on Ti6Al4V and cp-Ti alloys in two different electrolytes have been investigated. Additionally, molybdenum disulfide friction modifier (FM) was impregnated onto the PEO coatings to evaluate the effect of solid lubrication and composite nature of the ceramic PEO coating on tribological behaviour. Surface morphology and cross-sections were examined by scanning electron microscopy. Phase composition was identified by X-ray diffraction. Nanoindentations were performed to determine the mechanical properties of the coatings. Adhesion strength of the coatings was determined using a scratch test. To assess the tribological behaviour of the coatings, dry sliding wear test against 100Cr6 steel ball was performed with a ball on flat configuration. Test results showed that the PEO coating produced in aluminate–phosphate electrolyte possessed less wear loss compared to that produced in silicate–phosphate electrolyte. Impregnation of the PEO coatings with FM resulted in reduced friction coefficient.